Being a Nursing Graduate but Not Working as a Nurse: A Qualitative Study on Early Career Attrition from the Profession - Miray Aksu; Belgin Varol (Global Nursing Insights, 2026)
Aim: This study aimed to explore the experiences of nurses who left the profession within the first two years of completing their undergraduate nursing education, identify the factors contributing to early-career attrition, and examine proposed solutions to address this issue.Material and Methods: A phenomenological qualitative research design was employed. The study included 15 nurses who had left the nursing profession within two years following graduation. Participants were selected through purposive and snowball sampling methods. Data were collected through semi-structured individual interviews and analyzed using Colaizzi’s phenomenological analysis method. The research process was reported in accordance with the Consolidated Criteria for Reporting Qualitative Research guidelines.Results: The findings indicated that early-career attrition resulted from interacting factors at the individual, institutional, and systemic levels. At the individual level, burnout, anxiety, sleep disturbances, and emotional strain were prominent. Institutional factors included insufficient managerial support, unfair workload distribution, lack of resources, and exposure to workplace violence. At the systemic level, low salaries, insecure employment conditions, and the declining societal value of the nursing profession contributed to early departure. Additionally, the mismatch between expectations developed in nursing education and the realities of clinical practice weakened professional identity and increased the tendency to leave the profession. Participants particularly emphasized the absence of supportive leadership, fair shift scheduling, and mentoring systems.Conclusions: Improving the retention of newly graduated nurses requires coordinated interventions in education, health policy, and clinical management. Strengthening practice-oriented education, ensuring fair remuneration and safe working conditions, and promoting supportive leadership and mentorship are essential to enhancing professional commitment and supporting the sustainability of healthcare systems.Implication for nursing management: This study provides evidence-based findings on nursing management practices to support newly graduated nurses.